2000
DOI: 10.1021/jp9944381
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Surface States in the Ultrafast Photoinduced Electron Transfer from Sensitizing Dye Molecules to Semiconductor Colloids

Abstract: Investigations on the ultrafast electron injection mechanism from the dye alizarin to wide band gap semiconductor colloids in aqueous medium are presented, combined with detailed studies on population, depopulation, and relaxation phenomena in trap states and their influence on the injection process. Because of the very strong electronic coupling between dye and semiconductor in an alizarin/TiO 2 system, a very fast electron injection from the excited dye to the conduction band of TiO 2 is expected. Our measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

38
437
6
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 269 publications
(482 citation statements)
references
References 49 publications
38
437
6
1
Order By: Relevance
“…We note however that several groups have reported fast, < 100 fs, electron injection kinetics for other 5 metal oxide films, and discussed such kinetics both in terms of adiabatic electron transfer theory, and "hot" electron injection from unrelaxed dye excited states. 5,7,10,12 Given the complexity of our observed electron injection kinetics, it is possible that the fast (<150 fs) phase of injection, which accounts for up to 40% of the total injection yield at moderate potentials, may correspond to such processes. However such considerations are not necessary to account for the overall behavior of the electron injection kinetics of the RuL 2 (NCS) 2 -sensitized TiO 2 films studied in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…We note however that several groups have reported fast, < 100 fs, electron injection kinetics for other 5 metal oxide films, and discussed such kinetics both in terms of adiabatic electron transfer theory, and "hot" electron injection from unrelaxed dye excited states. 5,7,10,12 Given the complexity of our observed electron injection kinetics, it is possible that the fast (<150 fs) phase of injection, which accounts for up to 40% of the total injection yield at moderate potentials, may correspond to such processes. However such considerations are not necessary to account for the overall behavior of the electron injection kinetics of the RuL 2 (NCS) 2 -sensitized TiO 2 films studied in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…Such complex dynamics are not unusual and were reported previously for the system alizarin-ZrO 2 . 49 …”
Section: Transient Absorption Of D35 On Zromentioning
confidence: 99%
“…1,2 Recent ultrafast studies have shown charge injection from excited dye molecules into the conduction band of oxide semiconductors to occur in the femtosecond to picosecond time domain. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The time constant for ET has been found in these studies to vary from 6 fs 7 to hundreds of ps. [16][17][18] Charge transfer times 50 fs indicate that the corresponding electronic coupling strengths are approaching the value of the thermal energy kT (~ 200 cm -1 ) and, thus, that the reactions are likely to have reached the adiabatic limit.…”
Section: Introductionmentioning
confidence: 71%